Cryptocurrency trading and its associations with gambling and mental health: A scoping review. (January 2023) - Johnson, Benjamin; Co, Steven; Sun, Tianze; Lim, Carmen C.W.; Stjepanović, Daniel; Leung, Janni; Saunders, John B.; Chan, Gary C.K.
Abstract: Background and aims: The volatile and 24/7 nature of the cryptocurrency market allows traders to engage in speculative trading patterns closely resembling gambling. Its potential for harm and financial loss warrant investigation from a public health perspective . Therefore, we summarized the emerging literature on cryptocurrency trading and its link to problematic gambling and other mental health outcomes such as depression and anxiety. We also examined demographic or psychological factors associated with cryptocurrency trading. Methods: We searched PubMed, Scopus, and Embase for published, original studies investigating associations with cryptocurrency trading behavior. We also conducted supplementary searches using Google Scholar. Results: Eight papers were included after eligibility screening. Our scoping review revealed associations between problem gambling symptoms and cryptocurrency trading engagement and intensity. Furthermore, we found cryptocurrency traders share similar demographic and personality characteristics with share-traders and problem gamblers. Studies on cryptocurrency trading and mental health produced mixed results. Discussions and Conclusions: Our scoping review indicates a likely relationship between problem gambling and cryptocurrency trading. Findings also suggest overlap with high-risk stock traders, with similarities in gambling behaviors, demographics, and personality traits. These findings justify further research into problem cryptocurrency trading behaviors and their potential for harm, especially concerning mental health . To assess what behaviors are problematic, future research should also look to explore differences between long-term investors and short-term traders of cryptocurrency.